2018
DOI: 10.31958/jt.v21i1.1099
|View full text |Cite
|
Sign up to set email alerts
|

Obstacles Encountered While Integrating Literature in Teaching English

Abstract: This article depicts problems faced by High School teachers while using literature in teaching English. The data related to their broad views of using literature in the classroom were obtained from semi structured questionnaires as the preliminary data distributed to English teachers in Tanah Datar regency. As the result, by using purposive sampling technique ten of the teachers were selected to be the informants of the research. Then, in-depth interviews were conducted to the informants in order to find the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The main challenge faced in using literary texts in English classroom is the language of the texts selected which include the difficulties to understand the texts especially for low English proficient students (Othman et al, 2015;Krishnasamy, 2015;Hassan, 2018;Yulnetri, 2018;Lock & Zainal, 2020). Although teachers are equipped with ample of knowledge and proficient with the language itself, it does not mean that they can deliver it effectively (Cheung, 2019).…”
Section: Challenges In Using Literary Texts In English Classroom Text...mentioning
confidence: 99%
See 1 more Smart Citation
“…The main challenge faced in using literary texts in English classroom is the language of the texts selected which include the difficulties to understand the texts especially for low English proficient students (Othman et al, 2015;Krishnasamy, 2015;Hassan, 2018;Yulnetri, 2018;Lock & Zainal, 2020). Although teachers are equipped with ample of knowledge and proficient with the language itself, it does not mean that they can deliver it effectively (Cheung, 2019).…”
Section: Challenges In Using Literary Texts In English Classroom Text...mentioning
confidence: 99%
“…It is suggested that teachers should be trained and self-explore to impart knowledge and skills in teaching of literature. Besides, it is a challenge to teach literary texts without supporting tools and limited materials and resources (Yulnetri, 2018). Creative and innovative teaching tools should be provided by the schools and teachers to boost students' interest in learning literary texts.…”
Section: Teachers' Teaching Skills and Practicesmentioning
confidence: 99%